2018
DOI: 10.1186/s13023-018-0893-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of cognitive functioning in early treated adults with phenylketonuria

Abstract: BackgroundEven though early dietary management of phenylketonuria (PKU) successfully prevents severe neurological impairments, deficits in cognitive functioning are still observed. These deficits are believed to be the result of elevated levels of phenylalanine throughout life. Research on cognitive functioning in adults with PKU (AwPKU) often focuses on domains shown to be compromised in children with PKU, such as attention and executive functions, whereas other cognitive domains have received less attention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 73 publications
6
77
0
2
Order By: Relevance
“…Despite treatment, subtle cognitive deficits are still observed in ETAwPKU. [28][29][30] Underlying mechanisms are still under debate, and there is wide inter-individual variability, but such deficits have been associated with observed disruptions in brain pathophysiology (eg, demyelination and disturbed neurotransmitter synthesis). Some observed disruptions are similar to those seen in healthy ageing, but occur at a younger age in ETAwPKU (see Box 2).…”
Section: Brain Healthmentioning
confidence: 99%
“…Despite treatment, subtle cognitive deficits are still observed in ETAwPKU. [28][29][30] Underlying mechanisms are still under debate, and there is wide inter-individual variability, but such deficits have been associated with observed disruptions in brain pathophysiology (eg, demyelination and disturbed neurotransmitter synthesis). Some observed disruptions are similar to those seen in healthy ageing, but occur at a younger age in ETAwPKU (see Box 2).…”
Section: Brain Healthmentioning
confidence: 99%
“…12,29,33,[49][50][51] The quality of identified studies was assessed by a single author (RL) using the Quality Assessment Tool for Studies with Diverse Design. Further goals were to collect evidence on psychometric properties of these instruments in the identified studies, to explore how the authors justify instrument selection for a particular NDD and the respective group(s) of respondents, and to explore authors' concerns regarding the use of instruments and the respondent type.…”
Section: Analytic Consideration and Quality Appraisalmentioning
confidence: 99%
“…They are transported to the brain by the same amino acid transporter in the blood–brain barrier. In PKU, elevated plasma Phe levels impair the transport of other LNAAs, resulting in cerebral depletion of LNAA and hence decreased biosynthesis of protein and impaired brain function . Increased cerebral Phe competes with Gly and Glu for their receptors, changing the levels of receptor expression and thus influencing the synaptic function .…”
Section: Introductionmentioning
confidence: 99%
“…In PKU, elevated plasma Phe levels impair the transport of other LNAAs, resulting in cerebral depletion of LNAA and hence decreased biosynthesis of protein and impaired brain function. 8,15 Increased cerebral Phe competes with Gly and Glu for their receptors, changing the levels of receptor expression and thus influencing the synaptic function. 16 A previous study reported that the glutamatergic synaptic transmission in the brain is impaired in patients with PKU.…”
Section: Introductionmentioning
confidence: 99%